Interview with Tatiana Karabchuk. International Comparisons, Social Impacts of Labor Instability, and the Secrets of Academic Happiness - Karabchuk, Tatiana (Journal of Economic Sociology, 2019)
Tatiana Karabchuk, Assistant Professor of the College of Humanities and Social Sciences of the United Arab Emirates University, was interviewed by Elena Berdysheva, Senior Research Fellow at the Laboratory for Studies in Economic Sociology at the National Research University Higher School of Economics, in November 2018. The interview mainly focused on Karabchuk’s research interests and rich work experience at different universities around the world, emphasizing the differences in the academic infrastructures. Dr. Karabchuk highlights the shift toward international comparisons of studies in job stability, subjective well-being and happiness, and fertility and family policies. She claims that societies need to develop an understanding of how social and political institutions should be designed. Developing countries often implement social policies and practices borrowed from more developed ones. In this sense, social sciences can contribute to the process. Dr. Karabchuk also mentions the challenges for the social sciences in the UAE and her experience in launching a regular individual survey for data collection, ‘Monitoring of Emirati Youth’. Research efficiency in academia as well as the development of doctoral education in the UAE were other aspects highlighted in the interview. According to her comments, many universities today provide a productive infrastructure for research, which is a crucial determinant of success. In places where the environment is enriched with material, technical, and communication resources, academics are far more productive. Flexibility in timing and 24-hour office availability for the researchers are the most encouraging factors for productive work.